Informative Nagari based on Android and IoS in Nagari VII Koto Talago, Guguk Sub-district, Limapuluh Kota Regency - Ganefri Ganefri; Erianjoni Erianjoni; Mira Hasti Hasmira; Ahmaddul Hadi; Alfajri Yusra; Titen Darlis Santi (Pascasarjana, Universitas Negeri Padang, 2022)
Nagari VII Koto Talago, Guguk Sub-district, Lima Puluh Kota Regency, is a Nagari that has been classified as an Advanced Village by the Indonesian Ministry of Villages since 2021. However, from the point of view of its assessment, there is one variable that is still low, namely the absence of a pattern of public information disclosure (KIP) regarding the implementation of the Nagari government. If this rule regarding information disclosure is applied to practice in Nagari Government, then the Nagari Government must appoint a PPID so that the Nagari Government can properly manage information related to programs, activities, policies, and various other documentation regarding the administration of Nagari governance. With good information management, it is ensured that information services to the Nagari community will also be good so that the obligations of information disclosure as stipulated in the Village Law can be carried out optimally. Through the development of a Nagari web-based and Android-based Public Service Information System Application that can provide valid information about any programs carried out by the Nagari government, it can be seen by the public.